2019
DOI: 10.1016/j.toxrep.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

FTIR study of the binary effect of titanium dioxide nanoparticles (nTiO2) and copper (Cu2+) on the biochemical constituents of liver tissues of catfish (Clarias gariepinus)

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Among different techniques, Fourier transform-infrared (FTIR) spectroscopy, a form of vibrational spectroscopy, is one common analytical platform used in metabolic fingerprinting. It has been successfully applied to differentiate functional biochemical groups in the liver of fish exposed to different rearing conditions 11 , 12 , to determine the changes caused by spoilage in gilthead seabream 13 and salmon 14 , and to identify alterations provoked by toxic chemicals, in rainbow trout 15 , 16 , rohu 17 , 18 , Mozambique tilapia 19 and catfish 20 . Furthermore, FTIR spectroscopy was also applied to assess cod liver oil quality 21 and characterize hake lipids and lipid changes during frozen storage 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Among different techniques, Fourier transform-infrared (FTIR) spectroscopy, a form of vibrational spectroscopy, is one common analytical platform used in metabolic fingerprinting. It has been successfully applied to differentiate functional biochemical groups in the liver of fish exposed to different rearing conditions 11 , 12 , to determine the changes caused by spoilage in gilthead seabream 13 and salmon 14 , and to identify alterations provoked by toxic chemicals, in rainbow trout 15 , 16 , rohu 17 , 18 , Mozambique tilapia 19 and catfish 20 . Furthermore, FTIR spectroscopy was also applied to assess cod liver oil quality 21 and characterize hake lipids and lipid changes during frozen storage 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The biosafety of potential bone implants is an important factor that should be considered before approving biomaterials. The importance of this parameter was stressed out in previous studies 7,49‐51 . Compared to control sections obtained from normal dogs Figure 12(a), (c), the classic hepatic lobules of the liver of dogs treated with wollastonite doped with iron oxide appeared like normal (Figure 12(b)).…”
Section: Resultsmentioning
confidence: 81%
“…The importance of this parameter was stressed out in previous studies. 7,[49][50][51] Compared to control sections obtained from normal dogs Figure 12 It is concluded that iron oxide existence resulted in significantly higher mean bone density measurements compared to control and pure wollastonite, this could be explained by the fact that iron oxide is a major trace elements in bone that acts as scavenger for the removal of reactive oxygen species and other free radicals. This in turn prevents osteoclastic resorption and increases the osteogenic potential of iron oxide doped wollastonite.…”
Section: Coronal Along the Whole Study Regardless Timementioning
confidence: 98%
“…TiO 2 as metal oxide NPs is capable of binding to phosphate and/or nitrogenous base residues of DNA, which may lead to alterations of DNA structure. It can also interfere with proteins that function by stabilizing and repairing DNA damage (Federici et al, 2007;Matouke, 2019;Matouke and Mustapha, 2020). The ability of TiO 2 NPs to induce MN in the fish may likely be due to the production of hydroxyl radicals as a result of their photocatalytic property.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown the cytogenotoxic effects of TiO 2 NPs in crustaceans (Lovern and Klaper, 2006), Carassus auratus (Reeves et al, 2008), Oncochynchus mykiss (Ramsden et al, 2009), Cyprinus carpio (Sun et al, 2009), Daphnia magna (Zhu et al, 2010), Danio rerio (Rocco et al, 2015;Xiong et al, 2011), algae (Metzlera et al, 2011), mice (Fadoju et al, 2019) and Allium cepa (Fadoju et al, 2020). In a recent study, TiO 2 NPs and copper (Cu 2þ ) as binary mixture caused marked histological damages and alteration in protein secondary structures by decreasing the turns of liver tissues in Clarias gariepinus (Matouke, 2019). Likewise, Matouke and Mustapha (2020) showed that the binary mixtures of TiO 2 NPs and lead provoked a significant decrease in malondialdehyde, catalase, glutathione reductase and glutathione peroxidase levels.…”
Section: Introductionmentioning
confidence: 99%